Tafsir Desain Kursi di Keraton dan Gedung Agung Yogyakarta - Eddy Supriyatna MZ (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2010)
Chair is one of the unique visual arts (designs). The Indonesian word 'kursi' is possibly derived from the Arabic word 'kursiyun' which means chair. The term 'kursiyun' which is assumed originally from Kursi verses in Al-Qur'an has different functions and meanings in different contexts. In a social context, chairs are attributes that can be used to present a person's social status and prestige. It was found that in the Palace and Gedung Agung of Yogyakarta, a chair does not only function as a place for sitting, but it also serves as a symbolic tool for status display to build an image. Thus, it can also be used as a tool to show wealth, greatness, honor, glory, or a symbol of social status.